Neuropatia periférica induzida por quimioterapia e sua associação com quedas e síndrome das pernas inquietas - Ferreira, Lis Campos (2018)
Introduction: Chemotherapy-induced peripheral neuropathy (CIPN) is a common and often dose-limiting side effect. Restless Legs Syndrome (RLS) is also a common sensory-motor neurological disorder, characterized by uncomfortable and unpleasant sensations in the legs, followed by an urgency to move them. The presence of CIPN has been associated with the risk of falls in cancer survivors. Objectives: To determine the frequency and factors associated with falls in chemotherapy patients, and to evaluate the possible association between suggestive symptoms of CIPN, RLS and falls. Design: A total of 234 oncological patients undergoing chemotherapy treatment were interviewed, with questions regarding sociodemographic data, diagnosis, treatment and occurrence of falls. Besides, it was used the Chemotherapy Induced Peripheral Neuropathy Assessment Tool (CIPNAT) and diagnostic criteria for SPI. Results: The mean age of the sample was 53.4 years (± 13.1), of which 73.9% were female. Suggestive symptoms of CIPN were present in 51.7% of the patients, and falls were reported in 30.7%. There was association between the presence of neuropathic symptoms and falls (p = 0.0191), with a 1.65 fold increase in the prevalence of falls compared to patients without neuropathic symptoms. In individuals younger than 65 years of age, we observed a greater association between CIPN symptoms and falls (p = 0.0016). Patients with falls had a higher score on items that assessed interference in daily life activities. In addition, there was also a statistically significant association of RLS with symptoms of CIPN (p = 0.0005), RLS with falls (p = 0.0152), and RLS associated with neuropathic symptoms with falls (p = 0.0061). Conclusions: The findings of the present study suggest that falls are common in chemotherapy patients, and symptoms of CIPN and RLS contribute to increased falls. Moreover, these two disorders, when associated, act synergistically, further increasing the prevalence of falls.